Investigation of the Pentathiepin Functionality as an Inhibitor of Feline Immunodeficiency Virus (FIV) via a Potential Zinc Ejection Mechanism, as a Model for HIV Infection. (25th January 2019) - Asquith, Christopher R. M.; Laitinen, Tuomo; Konstantinova, Lidia S.; Tizzard, Graham; Poso, Antti; Rakitin, Oleg A.; Hofmann‐Lehmann, Regina; Hilton, Stephen T.
Abstract: A small diverse library of pentathiepin derivatives were prepared to evaluate their efficacy against the nucleocapsid protein function of the feline immunodeficiency virus (FIV) as a model for HIV, using an in vitro cell culture approach. This study led to the development of nanomolar active compounds with low toxicity. Abstract : A diverse library of pentathiepin derivatives were prepared which showed nanomolar efficacy against FIV in cells. The low molecular weight and toxicity make these compounds interesting starting points for future development of a nucleocapsid inhibitor. The structure of these compounds and potential mechanism of action was also probed, resulting in the identification of the S2−S3 position as the likely initial step of the zinc ejection mechanism.